Kriteria pemilihan dan prinsip pemanfaatan media pembelajaran berbasis TIK sesuai kebutuhan peserta didik - Miftah, Mohamad; Nur Rokhman (Educenter : Jurnal Ilmiah Pendidikan, 2022)
The use of ICT as a learning resource and media can be through the use of computer and mobile/smartphone devices as innovative learning resources and media. The purpose of writing the article is to share how to know the selection criteria for learning media and the selection procedure according to the needs of students. The research method used is library research. The research data is based on the findings of previous studies and studies, some underlying theories, and empirical findings. Researchers become developers, teaching/instructors of ICT-based learning media. The result of the research is that the selection criteria and the principles of using ICT as a learning medium are the basis and key to the success of learning outcomes. The teacher's role is very important in mastering ICT skills and mastering the ability to choose media and the principles of using ICT correctly and appropriately according to the needs of students and learning objectives. This library research is expected to be a material for wealth and literacy for teachers and developers of ICT based learning media at the conceptual and applied level.